Integrating models to quantify environment mediated drug resistance - Picco, N; Sahai, E; Maini, P; Anderson, A (American Association for Cancer Research, 2017)
Drug resistance is the single most important driver of cancer treatment failure for modern targeted therapies, and the dialogue between tumor and stroma has been shown to modulate the response to molecularly targeted therapies through proliferative and survival signaling. In this work, we investigate interactions between a growing tumor and its surrounding stroma and their role in facilitating the emergence of drug resistance. We used mathematical modeling as a theoretical framework to bridge between experimental models and scales, with the aim of separating intrinsic and extrinsic components of resistance in BRAFmutated melanoma; the model describes tumor-stroma dynamics both with and without treatment. Integration of experimental data into our model revealed significant variation in either the intensity of stromal promotion or intrinsic tissue carrying capacity across animal replicates.